Bezafibrate for the treatment of dyslipidemia in patients with coronary artery disease: 20-year mortality follow-up of the BIP randomized control trial. Issue 1 (December 2016) - Arbel, Yaron; Klempfner, Robert; Erez, Aharon; Goldenberg, Ilan; Benzekry, Sagit; Shlomo, Nir; Fisman, Enrique; Tenenbaum, Alexander
Abstract Background Recent data support the renewed interest in hypertriglyceridemia as a possible important therapeutic target for cardiovascular risk reduction. This study was designed to address the question of all-cause mortality during extended follow-up of the BIP trial in patients stratified by baseline triglyceride levels. Methods In the BIP trial 3090 patients with proven coronary artery disease were randomized to bezafibrate 400 mg/day or placebo. All-cause mortality data after 20 years of follow-up, were obtained from the National Israeli Population Registry. Patients with hypertriglyceridemia (triglycerides ≥200 mg/dL, n = 458) were equally distributed among the study groups (15 % in both placebo and bezafibrate groups). Results During follow-up 1869 patients died (952 in placebo vs. 917 in bezafibrate group). Following multivariate adjustment allocation to bezafibrate was associated with small but significant 10 % mortality risk reduction (HR 0.90; 95 % CI 0.82–0.98, p = 0.026). Variables associated with significantly increased mortality risk were history of a past MI, NYHA class, diabetes, age, higher BMI and glucose level. In patients with hypertriglyceridemia multivariate analysis demonstrated a 25 % all-cause mortality risk reduction associated with allocation to bezafibrate (HR 0.75, CI 95 % 0.60–0.94; p = 0.012). In patients without hypertriglyceridemia bezafibrate had no significant effect on long-term mortality. Conclusions During long-term follow-up bezafibrate-allocated patients experienced a modest but significant 10 % reduction in the adjusted risk of mortality. This effect of bezafibrate was more prominent among patients with baseline hypertriglyceridemia (25 % mortality risk reduction).